BESPOKE study protocol: a multicentre, prospective observational study to evaluate the impact of circulating tumour DNA guided therapy on patients with colorectal cancer - Scott Kopetz; Axel Grothey; Shifra Krinshpun; Meenakshi Malhotra; Paul Billings; Angel Rodriguez; Alexey Aleshin; Sarah Sawyer; Michelle Munro; Pashtoon Murtaza Kasi; Jessica Guilford; Sascha Ellers; et al. (BMJ Open)
Introduction Colorectal cancer (CRC) is a highly prevalent disease, wherein, ~30%–40% of patients with CRC relapse postresection. In some patients with CRC, adjuvant chemotherapy can help delay recurrence or be curative. However, current biomarkers show limited clinical utility in determining if/when chemotherapy should be administered, to provide benefit. Circulating tumour DNA (ctDNA) can measure molecular residual disease (MRD) and relapse with high specificity and sensitivity. This study protocol investigates the clinical utility of ctDNA for optimal use of adjuvant chemotherapy in patients with surgically resected CRC and to detect early disease progression in the surveillance setting.Methods and analysis This is a multicentre prospective, observational cohort study. A total of 2000 stage I–IV patients will be enrolled in up to 200 US sites, and patients will be followed for up to 2 years with serial ctDNA analysis, timed with the standard-of-care visits. The primary endpoints are to observe the impact of bespoke ctDNA testing on adjuvant treatment decisions and to measure CRC recurrence rates while asymptomatic and without imaging correlate. The secondary endpoints are MRD clearance rate (MRD+ to MRD−) during or after adjuvant chemotherapy, percentage of patients that undergo surgery for oligometastatic recurrence, survival of MRD-negative patients treated with adjuvant chemotherapy versus no adjuvant chemotherapy (active surveillance), overall survival, examine the number of stage I CRC that have recurrent disease detected postsurgery, and patient-reported outcomes.Ethics and dissemination This study has received ethical approval from the Advarra Institutional Review Board (IRB) protocol: Natera—20-041-NCP/3766.01, BESPOKE Study of ctDNA Guided Therapy in Colorectal Cancer (BESPOKE CRC) (Pro00041473) on 10 June 2021. Data protection and privacy regulations will be strictly observed in the capturing, forwarding, processing and storing of patients’ data. Publication of any study results will be approved by Natera in accordance with the site-specific contract.Trial registration number NCT04264702.